Factores asociados al mal apego del tratamiento antihipertensivo en pacientes de la consulta externa de medicina familiar del HGZMF No.2 de diciembre 2022 a mayo 2023 - Díaz García, Karla Paola (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Introduction: Systemic arterial hypertension is a disease caused by behavioral risk factors such as an unhealthy diet, physical inactivity and other metabolic factors such as obesity, diabetes and dyslipidemias. Objective: To determine the main factors associated with poor adherence to antihypertensive treatment in men and women in the family medicine outpatient clinic of HGZ/MF No.2 from December 2022 to May 2023. Material and methods: A descriptive cross-sectional study of 364 hypertensive patients over 18 years of age from the family medicine outpatient clinic of HGZ/MF NO.2 from December 2022 to May 2023. The 8-item Morisky Medication Adherence Scale (MMAS-8) was applied, with Cronbach's alpha of 0.693, descriptive statistics and chi2 were performed to determine the association between categorical variables with a significant value p<0.05. Registration number: R-2023-1603-005. Results: A total of 364 hypertensive patients were surveyed, mainly women, over 60 years of age, with secondary education and married. Poor therapeutic adherence was determined in 64% of the surveyed population, predominating in men, over 60 years of age, married, with secondary education and with combined therapy in 72.91%. A relationship was found between good adherence and adequate BP control (p<0.001). Conclusions: Low therapeutic adherence occurred in 34.90% of the population. A relationship was found between BP control and medication adherence, so it is essential that the primary care physician supervises and insists on good adherence to treatment to achieve adequate metabolic control.

Introducción: La hipertensión arterial sistémica es una enfermedad producida por factores de riesgo conductuales como una dieta poco saludable, inactividad física y otros factores metabólicos como obesidad, diabetes y dislipidemias. Objetivo: Determinar los principales factores asociados a la baja adherencia a la medicación antihipertensiva en hombres y mujeres de la consulta externa de medicina familiar del HGZ/MF No.2 de diciembre 2022 a mayo 2023. Material y métodos: Estudio transversal descriptivo, a 364 pacientes, hipertensos, mayores de 18 años, de la consulta externa de medicina familiar del HGZ/MF NO.2, de diciembre 2022 a mayo 2023. Se aplicó la Escala de Adherencia a la Medicación de Morisky 8 ítems (MMAS-8), con alfa de Cronbach de 0.693, se realizó estadística descriptiva y chi2 para determinar la asociación entre variables categóricas con valor significativo p<0.05. Número Registro: R-2023-1603-005. Resultados: Se encuestaron 364 pacientes hipertensos, principalmente mujeres, mayores de 60 años, con escolaridad secundaria y casados. Se determinó una baja adherencia a la medicación en el 34.90% de la población, predominando en mujeres, mayores de 60 años, casadas, con escolaridad secundaria y terapia combinada 16.8%. Se encontró relación entre el grado de control de TA con la adherencia a la medicación (p<0.001). Conclusiones: La baja adherencia terapéutica se presentó en el 34.90% de la población. Se encontró relación entre el control de TA con la adherencia a la medicación, por lo que es fundamental que el médico de primer nivel supervise e insista en el buen apego al tratamiento para lograr un adecuado control metabólico.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2025-0080; Hipertensión arterial sistémica; Factores asociados; Adherencia terapéutica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19073